PBAT biocomposites reinforced with açaí seed residues: Exploring sustainable material development - Odilon Leite-Barbosa; Mateus Santos da Silva; Debora Cristina da Silva Santos; Fernanda Cristina Fernandes Braga; Marcelo Ferreira Leão de Oliveira; Marcia Gomes de Oliveira; Sérgio Neves Monteiro; Valdir Florêncio Veiga-Junior (Journal of Materials Research and Technology)
Developing sustainable materials is essential for advancing eco-friendly technologies and promoting circular economy practices. This study investigates the reinforcement of poly(butylene adipate-co-terephthalate) (PBAT) with açaí seed residues (ASR), an abundant agro-industrial byproduct from Brazil. The residues were characterized using FTIR, XRD, TGA, and SEM, while the biocomposites underwent mechanical, morphological, and thermal evaluations. Composites were prepared by mixing PBAT with 20 wt% and 40 wt% of ASR in an internal mixer equipped with ROLLER-type rotors, followed by injection molding. Compared to neat PBAT, the incorporation of ASR resulted in a 37 % and 53 % reduction in tensile strength (from 19.71 MPa to 12.37 MPa and 9.19 MPa, respectively). The elastic modulus increased by 8.8 % and 20.1 %. Yield strength remained relatively stable, with values of 9.75 MPa (PBAT), 10.79 MPa (20 % ASR), and 9.29 MPa (40 % ASR). The total strain at break decreased from 239 % (neat PBAT) to 150 % (20 % ASR) and 121 % (40 % ASR). Flexural strength increased by 39 %, from 7.5 MPa to 10.4 MPa at 40 % ASR, while flexural modulus rose by 62 %, from 191 MPa to 310 MPa. Thermal analysis revealed a nucleating effect of the filler, elevating the crystallization temperature from 65.55 °C to 79.90 °C. The thermal resistance of all biocomposites showed a similar weight loss curve profile as a function of temperature, with a slight reduction in the initial degradation temperature (Tonset) compared to neat PBAT. Water absorption rose from 0.50 % in neat PBAT to 3.75 % at 40 % filler, attributed to the hydrophilic nature of the residues. These findings highlight the potential of açaí seed residues as reinforcement in the development of polymer biocomposites for sustainable applications.